Pengaruh Cash Ratio dan Siklus Konversi Kas Terhadap Profitabilitas Perusahaan - Susilawati, Nisa; Supriadi, Yoyon (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
Profit in a company’s operation is an important element to ensure the survival of the company in the future. The company’s success can be measured from its ability in creating profits derived from committed financing, its competitiveness in the market, and its ability company to expand the business. The company’s ability to generate profits from its business activities is called profitability. The purpose of this research is to determine the effects of operating cycle and Cash Conversion Cycle on the Profitability of the company, respresented by ROA (return on asset). The study was conducted at PT. Indocement Tunggal Prakarsa, Tbk, PT. Semen Gresik (Persero), Tbk and PT. Holcim Indonesia, Tbk for ten years from 2005 to 2014. In this study, the data used are cash ratio, cash conversion cycle and the financial statement (balance sheet and income statement) PT. Indocement Tunggal Prakarsa, Tbk, PT. Semen Gresik (Persero), Tbk and PT. Holcim Indonesia, Tbk period 2005 to 2014. Analysis of the data used is the linear regression analysis and determination coefficient, T test and F test. The study conclude that the of operating cycle has partially significant effect on profitability of PT. Holcim Indonesia, Tbk , because Sig. 0,009 is less than the standard error or alpha (α) of 5%, the of cash conversion cycle has partially significant effect on profitability PT. Semen Gresik (Persero), Tbk , because Sig. 0,001 is less than the standard error or alpha (α) of 5%, and cash ratio and cash conversion cycle simultaneously have not significant effects on the PT. Indocement Tunggal Prakarsa, Tbk because Sig. 0,079 greater than the standard error or alpha (α) of 5%.